Overview of the Records Management Office Regional Library In East Kalimantan Province. - Muhdar, Anggun Rahmatika (PREDIKSI, 2014)
The purpose of this study is to describe and analyze how the Records Management In Regional Library East Kalimantan Province and identify factors supporting and inhibiting the implementation of the Records Management.Type of research include descriptive. The main focus of the study was to determine how to set Filing Procedures include, namely: Book Events Procedure, Procedure Control Card, Tata Scripts and Procedures. Storage includes two kinds of storage, namely: Temporary Storage (File Pending), and Storage Equipment (Permanent File), Maintenance includes archive room, covering lending and Services Oversight and Displacement and Destruction includes Assessor Records, Retention Schedule, Displacement and Destruction of records and archives Factor Inhibiting and Supporting. The types of data used include primary data and secondary data, while data sources are taken from informen competent, among which the Head of Sub Division of General, Head of Information and Library Automation, Head of Acquisitions and Processing, Sub Division General Executive Staff, and Staff Sub Planning Program. While data collection techniques by observation, interviews, and documentation. Analysis of the data used is interactive model developed by Miles and Huberman.